Reliability, validity, usefulness, and sensitivity of a submaximal test of performing burpees in 3 minutes, in assessing and detecting changes in aerobic fitness of athletes during future prolonged self-isolation in a confined environment - Tai, J. Q.; Wong, S. F.; Chow, S. K.; Choo, D. H.; Choo, H. C.; Yeo, V.; Sahrom, S.; Aziz, A. R. (The Journal of Sports Medicine and Physical Fitness, 2024)
BACKGROUND: During a prolonged quarantine, there is a need to monitor aerobic fitness levels of trained individuals who are isolated with a simple fitness test that can be performed in confined space of their own homes. This study examined the reliability, validity, usefulness and sensitivity of a novel 3-min submaximal heart rate burpees test (or SubHR3-MBT) to assess and monitor changes in aerobic fitness, of trained athletes. In the SubHR3-MBT, male and female athletes performed 48 and 39 burpees respectively, within 3 min by following a constant beeping pace. The performance criterion of the SubHR3-MBT is the highest heart rate attained (or exercise HRpeak) at the end of 3-min (wherein a lower exercise HRpeak indicates a higher level of aerobic fitness). METHODS: A total of 40 male and female national athletes from various sports volunteered for the study. RESULTS: For reliability (Part 1), the SubHR3-MBT showed good relative and excellent reliability, with intraclass correlation coefficient 0.90 and coefficient of variation 2.6%, respectively. For validity (Part II), there was significant negative correlation between relative exercise HRpeak with respiratory gas-measured VO2max (r=-0.51, large; P<0.001). The test`s technical error of measurement of 2.3 is slightly greater than its smallest worthwhile change of 1.5. For sensitivity (Part III), the athletes were tested twice for their SubHR3-MBT and VO2max, once at baseline and another at a followed-up test after >10 weeks. There was a significant correlation between the % change in relative exercise HRpeak with the % change in VO2max (r=-0.66, large; P<0.001). CONCLUSIONS: The SubHR3-MBT is a reliable, valid, marginally useful test and may be able to track changes in aerobic fitness in trained athletes with moderate levels of sensitivity, in case of future isolation due to pandemic occurrence.